PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA REALIA UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA MATERI PERUBAHAN WUJUD ZAT KELAS IV A UPTD SD NEGERI SIKUMANA 1 - Dasilva Mbela, Luysa; Elisabet Antoneta Nawa, Netty; Bol Nifu Benu, Adam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve student learning outcomes in the science subject of changes in state of matter through the application of problem-based learning (PBL) with the aid of realia media in fourth-grade students at the Sikumana 1 Elementary School (UPTD) in Kupang City. The background of this study is based on low student learning outcomes and the teacher-centered learning process, resulting in less active student learning.This study used classroom action research (CAR) conducted in two cycles, with planning, implementation, observation, and reflection. The subjects were 18 fourth-grade students at the Sikumana 1 Elementary School (UPTD) in Kupang City. Data collection techniques were observation, learning achievement tests, and documentation. The results showed that the application of the PBL with the aid of realia media improved teacher activity, student activity, and student learning outcomes. In the first cycle, the average observation of teacher activity was 77.5 and student activity was 73.75, with a learning completion rate of 61%. After improvements were made in cycle II, the teacher's observation score increased to 92.5 and the student's score to 87.5, with a learning achievement of 89%. The comparison of learning outcomes between cycle I and cycle II was 27.77%. Based on these data, it can be concluded that implementing the problem-based learning model with the aid of realia media in the science subject of changes in the state of matter can improve student learning outcomes.